Pengaruh Motivasi dan Disiplin Kerja terhadap Prestasi Kerja Pegawai di Dinas Pendidikan dan Kebudayaan Kota Bontang - Sari, Nur Bulan Purnama; Putra, Dhimas Eka; Takwin, Muh. (Masyarakat Ekonomi Syariah Bogor, 2024)
Through this research, the researcher aims to investigate how motivation specifically influences the performance of employees in the Department of Education and Culture of Bontang City. The researcher also seeks to understand the dynamics of work motivation in the same office environment, and its impact on their performance. Thus, this study can shed a unique spotlight on the complex relationship between motivation and performance within the specific organizational context. The data for this research was processed using SPSS with a sample of 55 employees working in the Department of Education and Culture of Bontang City. Validity tests were conducted and all variables proved to be valid. Reliability tests ensured that the variables were dependable. Descriptive analysis results indicated very positive responses. Normality tests ensured that the data were normally distributed. Additionally, multicollinearity tests did not show multicollinearity symptoms. Heteroskedasticity tests concluded that there were no anomalies and the data variance was normally distributed. When multiple regression was conducted, a constant of 5.891 was obtained, with a regression coefficient for work discipline of 0.248 and a regression coefficient for motivation of 0.585. The results of hypothesis testing such as R2 test, T-test, and F-test indicated that work discipline and work motivation significantly influence employee performance. Strong motivation can drive high employee commitment, but work discipline also contributes to good commitment levels in the Department of Education and Culture of Bontang City. From this research, it can be concluded that besides work discipline individually, motivation also plays an equally important role. However, the interesting finding is that when motivation and work discipline are combined, their impact on the performance of employees in the Department of Education and Culture of Bontang City becomes significant. This indicates that the combination of these factors creates a greater force in shaping productivity and performance.